Neurofunctional evaluation in patients affected by leprosy - Rafael Mesquita; Luana Torres Monteiro Melo; Renata dos Santos Vasconcelos; Débora Militão Soares; George André Araújo Félix; Liana Parente de Azevedo Férrer; Ana Paula Vasconcellos Abdon (Universidade de Fortaleza, 2014)
Objective: To investigate neurofunctional alterations in patients affected by leprosy, also searching to identify their socioeconomic and clinical profile. Methods: Cross-sectional study with 51 adult patients diagnosed with leprosy, regardless of gender, conducted in a reference center in 2010, in which the simplified neurofunctional evaluation form and a questionnaire (socioeconomic and clinical data) were applied. Findings were presented in a descriptive approach. Results: The study found a mean age of 46.4 ± 14.9 years, 32 (62.7%) patients of male sex, 32 (62.7%) with incomplete elementary school and 37 (72.5%) with family income between 1 and 3 minimum wages. The mean time of treatment was 14.4 ± 15.63 months. The multibacillary type of leprosy predominated (n=18/35.3%) with tuberculoid form (n=11/21.6%). The interphalangeal joints of upper and lower limbs were compromised in 5 (9.8%) and 6 (11.7%) patients, respectively. The most affected nerves were the posterior tibial in 19 (37.3%), the ulnar in 17 (33.3%), and the common fibular in 13 (25.5%) patients. The muscles with deficit were the extensor hallucis (n=8/15.7%), the toe extensors (n=6/11.8%) and the 5º finger abductor (n=6/11.8%). It was observed that 35 patients (68.6%) presented sensitive alterations in lower limbs and 14 (27.5%) presented functional incapacity degree 1. Conclusion: The study highlighted the socioeconomic profile of leprosy patients as men, low educational level and income, with multibacillary operational classification showing tuberculoid clinical form. In the neurofunctional assessment, there were sensory changes with higher incidence than the motor alterations, as well as discreet presence of deformities and high degree of functional disability. doi:10.5020/18061230.2014.p247